Understanding unconventional medicine Social sciences on traditional, complementary and alternative therapies in Slovakia - Souček, Ivan (Masaryk University Press, 2022)
The phenomenon of unconventional medicine is an important feature of any contemporary society. Considering the increasing popularity of various forms of non-biomedical methods of healing among various groups of people, the necessity of an in-depth investigation of traditional, complementary and alternative therapies continues to grow. Existing terminology along with prevalence rates, legal status and historical development, vary greatly in European countries. The main reason behind the compilation of this publication was, therefore, to provide an overview of the field of unconventional medicine in Slovakia, where social science research into medicine has largely been neglected and only limited data exist in relation to medical practices and products, not associated with standard healthcare. Despite various concerns and controversies that have been raised regarding alternative medicine, the intent of the book is not to provoke criticism, the representatives of which are sufficiently represented in the public debate. Likewise, it does not try to reinforce the idealized and non-critical image of unconventional therapies, adopted by a number of alternative healthcare practitioners and providers. Rather than contribute to the polarization of the topic, the purpose of this monography is to provide a comprehensive understanding of the historical background of unconventional therapies, the main trends in this area, the patterns and reasons for the use of alternative medicine and the factors determining the efficacy of alternative therapies. The first section briefly introduces the historical development of the most notable forms of unconventional medicine in Slovakia, while highlighting various institutionalization and professionalization strategies, that have dominated over the last few decades. The second section mainly concerns a representative survey, investigating the patterns and trends of unconventional medicine use and concentrates on the execution of data on prevalence and types of non-conventional medicine, examining attitudes towards different topics related to alternative healthcare. Lastly, the book briefly enters the ongoing discussion as to how unconventional medicine might work and how efficacy is negotiated between the different actors involved in the healing process.